Influence of Training, Work Environment and Motivation on Employee Performance at the Cikarang Manufacturing Company - Situmorang, Desy; Anatan, Lina (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to analyze the effects of training, work environment, and motivation on employee performance at PT X, a manufacturing company located in Cikarang. The study adopts a quantitative approach and employs a non-probability sampling technique using purposive sampling. Data were collected through questionnaire distribution, and the data analysis was conducted using the Partial Least Squares (PLS) method with the assistance of SmartPLS 4 software, which includes the assessment of both the outer model and the inner model to examine the relationships among variables. A total of 146 respondents participated in this study, all of whom were employees of PT X. The results indicate that training has a negative and significant effect on employee performance, the work environment has a negative but insignificant effect on performance, while motivation has a positive and significant effect on employee performance. The most influential factors include compensation, job security, social relationships among employees, and employee recognition and appreciation in enhancing employee performance at PT X. The implications of this study suggest that the company needs to enhance employee motivation through a supportive work environment as well as a fair system of rewards and recognition, as these factors have been proven to positively affect performance. In addition, the company should evaluate and adjust its training programs to ensure they are more effective and relevant to job requirements. The current work environment should also be continuously maintained and improved so that it does not become a barrier to employee performance in the future. This study is important because it is expected to provide positive contributions to the company and assist human resource management in formulating strategies to improve employee performance, enabling the company to remain competitive amid uncertain economic conditions.